2014
DOI: 10.1371/journal.pcbi.1003668
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Sampling Strategies for Detecting Zoonotic Disease Epidemics

Abstract: The early detection of disease epidemics reduces the chance of successful introductions into new locales, minimizes the number of infections, and reduces the financial impact. We develop a framework to determine the optimal sampling strategy for disease detection in zoonotic host-vector epidemiological systems when a disease goes from below detectable levels to an epidemic. We find that if the time of disease introduction is known then the optimal sampling strategy can switch abruptly between sampling only fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…21 Delays in field activities could affect the integrity of the sample, depending on the type of the sample and the agent involved. 22,23 Previous work in our research group spent almost one day just to reach one allocated random point and then search for the closest BPS to sample (Di Pillo, F. data not published). According to the characteristics of these production systems, most birds or pigs are raised in partially enclosed systems, where animals are confined at night and released to an extensive rearing during the day, increasing the difficulty of sampling.…”
Section: Resultsmentioning
confidence: 99%
“…21 Delays in field activities could affect the integrity of the sample, depending on the type of the sample and the agent involved. 22,23 Previous work in our research group spent almost one day just to reach one allocated random point and then search for the closest BPS to sample (Di Pillo, F. data not published). According to the characteristics of these production systems, most birds or pigs are raised in partially enclosed systems, where animals are confined at night and released to an extensive rearing during the day, increasing the difficulty of sampling.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of surveillance within a host-vector system has been previously studied by Ferguson and others [ 65 ], who found that the relative prevalences and the costs of sampling determined the probability of detection in any group at any single sampling point. This shares similarities with our own formulation, since the ratio can be considered the ratio of prevalences amongst hosts and vectors during initial exponential growth.…”
Section: Discussionmentioning
confidence: 99%
“…This shares similarities with our own formulation, since the ratio can be considered the ratio of prevalences amongst hosts and vectors during initial exponential growth. As with our approach, the Ferguson model had threshold-like behaviour in which the optimal sampling strategy suddenly changed, with the optimal sampling strategy generally being to focus on a single group of interest [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, our scheme, so as many other standard immunization strategies, is strongly information-demanding. Of course, a full knowledge about the complex system is rather unlikely in real situations, then sampling and interpolation (Ferguson et al, 2014), so as data assimilative strategies (Rhodes and Hollingsworth, 2009) have been recently developed. The second aspect concerns the role of the tunable parameters in our strategy.…”
Section: Conclusion and Discussionmentioning
confidence: 99%